Case Report: Combination of sirolimus and endoscopic lauromacrogol sclerotherapy in the management of blue rubber bleb nevus syndrome with gastric tract bleeding - Liu, Lu; Wang, Liyuan; Hu, Fan (Frontiers in Pediatrics, 2025)
Blue rubber bleb nevus syndrome (BRBNS) is a rare kind of venous malformation. So far there was no standard therapy for this disease. Lauromacrogol is a sclerosant extensively utilized in the management of vascular malformations and is also applied in the treatment of BRBNS. Research on the combined therapy of sirolimus and lauromacrogol for BRBNS is limited.Hereby, we report a 12 years old girl with BRBNS. The patient presented with chronic anemia and skin "hemangioma". The examinations showed severe anemia, decreased serum iron and ferritin level. The magnetic resonance image showed abnormal nodular lesions at various parts of the intestine. Endoscopic sclerotherapy with lauromacrogol and oral sirolimus was combined to treat the patient. After 1 year, the patient showed no anemia or GI tract bleeding.BRBNS is a rare disorder that often leads to misdiagnosis, especially among inexperienced pediatricians. The combination of oral sirolimus with endoscopic lauromacrogol has demonstrated efficacy in the reduction of lesion size and elevation of hemoglobin levels.